2014
DOI: 10.1007/s10661-014-4001-5
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural practices in grasslands detected by spatial remote sensing

Abstract: The major decrease in grassland surfaces associated with changes in their management that has been observed in many regions of the earth during the last half century has major impacts on environmental and socio-economic systems. This study focuses on the identification of grassland management practices in an intensive agricultural watershed located in Brittany, France, by analyzing the intra-annual dynamics of the surface condition of vegetation using remotely sensed and field data. We studied the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 60 publications
(64 reference statements)
0
16
0
1
Order By: Relevance
“…Crop health indicators can potentially be used to determine a specific crop's health conditions during the growth cycle. Remote sensing researchers use Normalized Difference Vegetation Index (NDVI), Vegetation Index (VI), and Enhanced Vegetation Index (EVI) to investigate different crop help conditions (Dusseux, Vertès, Corpetti, Corgne, & Hubert-moy, 2014;Prasad, Chai, Singh, & Kafatos, 2006;Tang, Li, Chen, Zhu, & Liu, 2012). For example, NDVI, which represents the greenness and health of crops (Prasad et al, 2006), can be used as a variable to determine crop yield.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crop health indicators can potentially be used to determine a specific crop's health conditions during the growth cycle. Remote sensing researchers use Normalized Difference Vegetation Index (NDVI), Vegetation Index (VI), and Enhanced Vegetation Index (EVI) to investigate different crop help conditions (Dusseux, Vertès, Corpetti, Corgne, & Hubert-moy, 2014;Prasad, Chai, Singh, & Kafatos, 2006;Tang, Li, Chen, Zhu, & Liu, 2012). For example, NDVI, which represents the greenness and health of crops (Prasad et al, 2006), can be used as a variable to determine crop yield.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the European CORINE Land Cover layer, which is produced every 6 years at a 1:100,000 scale by visual analysis of high spatial resolution Landsat or Sentinel images [21], was used to model farms with high nature value in Europe using a 1 × 1 km grid [7] and semi-natural grasslands in France using a 5 × 5 km grid [22]. Beyond these broad-scale maps based on the CORINE Land Cover layer, many studies based on automatic and fine-scale analyses have demonstrated the contribution of multi-temporal and high-spatial-resolution satellite data in discriminating grasslands from other LULC types [16,[23][24][25], characterizing forage quality [20], identifying agricultural practices [26] and mapping floristic variation in semi-natural grasslands [27][28][29]. However, discriminating semi-natural and temporary grasslands accurately remains a concern [23,30] due to the lack of temporal depth in remote sensing time-series and because a one-year observation is insufficient to discriminate between semi-natural and temporary grasslands [31].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the characteristics of remote sensing data, the selection of the classifier and the reference data is crucial for successful LULC classification [42]. Semi-natural grasslands encompass a diversity of habitats [19] whose spectral response varies greatly according to agricultural practices [26], flood duration [43], snow duration [44], phenological stage [45] or percentage of bare soil cover [1]. Parametric classifiers, such as the maximum likelihood classifier, are generally of limited value for identifying grasslands [1].…”
Section: Introductionmentioning
confidence: 99%
“…Villalobos-Villalobos y WingChing-Jones: Estrategias de recuperación de pasturas 823 tiempo (Montagner et al, 2012). En países de clima templado se usa el segado como estrategia para reducir la altura del pasto y la biomasa remanente del ciclo de crecimiento anterior (otoño-invierno), previo al inicio del nuevo ciclo de crecimiento (primavera-verano) (Dusseux et al, 2014). Estrategias de este tipo permiten incrementar la uniformidad en pasturas (Tälle et al, 2016) y maximizar la eficiencia de cosecha del forraje producido en sistemas de pastoreo (Simioni et al, 2014).…”
Section: Introductionunclassified